An experimental and theoretical study of the coordination and donor properties of tris-2-pyridyl-phosphine ligands. Issue 16 (3rd April 2020) - Hanf, Schirin; Colebatch, Annie L.; Stehr, Philipp; García-Rodríguez, Raúl; Hey-Hawkins, Evamarie; Wright, Dominic S.
Abstract : The donor properties of a range of multidentate 2-pyridyl-phosphines were evaluated using different experimental and computational methods. Abstract : The coordination characteristics and donor/acceptor properties of a series of 2-pyridyl substituted phosphine ligands have been investigated using structural, spectroscopic and DFT calculational studies. A range of different coordination modes are observed in Mo and W carbonyl complexes of tris-2-pyridyl-phosphine ligands of the type P(2-py') (2-py' = substituted or unsubstituted 2-pyridyl group), including an unprecedented example exhibiting N, N ′, μ2 -π coordination. DFT calculations were used to assess the relative donor/acceptor properties of a range of related 2-pyridyl-phosphine ligands with respect to PPh3 and P t Bu3 .